2021
DOI: 10.1097/cmr.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of thyroid dysfunctions on progression-free survival in patients with metastatic melanoma treated with anti-PD-1 antibodies

Abstract: This study aimed to assess the prognostic value of thyroid dysfunctions in metastatic melanoma patients on anti-programmed death-1 (anti-PD-1). A total of 110 stage IV or inoperable stage III melanoma patients treated with anti-PD-1 alone or in association with anti-CTLA-4 (T-lymphocyte antigen-4) antibody from January 2015 to December 2017 at our institution were enrolled in this retrospective study. Median follow-up was 32.8 months. Transitory thyroid dysfunctions and permanent thyroid dysfunctions were dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In addition, patients with NSCLC, renal cell carcinoma and metastatic melanoma who received PD-1 inhibitors and acquired overt thyroid dysfunction exhibited improved OS and PFS than those without thyroid dysfunction ( 17 ). In the present study, general, thyroid dysfunction was associated with a longer PFS in Chinese patients receiving PD-1 inhibitors, which was similar to previous studies focusing of Caucasian cancer patients receiving PD-1 inhibitors ( 23 , 24 ). Thus, it could be deduced that the prognostic value of thyroid dysfunction was not affected by ethnicity, although further studies should verify this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, patients with NSCLC, renal cell carcinoma and metastatic melanoma who received PD-1 inhibitors and acquired overt thyroid dysfunction exhibited improved OS and PFS than those without thyroid dysfunction ( 17 ). In the present study, general, thyroid dysfunction was associated with a longer PFS in Chinese patients receiving PD-1 inhibitors, which was similar to previous studies focusing of Caucasian cancer patients receiving PD-1 inhibitors ( 23 , 24 ). Thus, it could be deduced that the prognostic value of thyroid dysfunction was not affected by ethnicity, although further studies should verify this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 57 studies included OS data ( 13 18 , 32 39 , 41 58 , 60 71 , 73 85 ) and 34 included PFS data ( 14 , 15 , 18 , 32 , 33 , 36 42 , 47 , 49 , 54 , 55 , 58 60 , 62 , 64 , 66 , 68 72 , 75 , 76 , 78 , 79 , 81 , 82 , 85 ). Geographically, 18 studies were from Asian countries ( 35 , 39 , 48 , 56 , 61 66 , 69 , 76 81 , 85 ), 24 from European countries ( 13 16 , 33 , 36 38 , 41 43 , 45 , 47 , 50 , 53 55 , 58 , 59 , 68 , 74 , 75 , 82 , 84 ), six from the United States ( 32 , 44 , 46 , 52 , 67 , 70 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 57 articles assessed the association between the occurrence of irAEs and OS in patients with melanoma ( 13 18 , 32 39 , 41 58 , 60 71 , 73 75 , 77 86 ), and 34 assessed PFS ( 14 , 15 , 18 , 32 , 34 , 36 42 , 47 , 49 , 54 , 55 , 58 60 , 62 , 64 , 66 , 68 72 , 75 , 76 , 78 , 79 , 81 , 82 , 85 ). Among these, the study of Abu-Sbeih et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that the occurrence of TD is a promising pronostic factor in cancer patients receiving ICIs, including lung cancer [ 17 , 18 ] and melanoma [ 26 ]. However, no research has investigated the association of TD and prognosis of ESCC.…”
Section: Discussionmentioning
confidence: 99%